A Randomised Control Study Comparing Hemodynamic Response to Laryngoscopy & Endotracheal Intubation with Macintosh Direct Laryngoscope & C-Mac Video Laryngoscope In Adult Patients - Anil Kumar, Valluri; Prithvi Raj, Busetty; Rajesh, V.S.P.; Chandradhar, A. Murali (Academia Anesthesiologica International, 2019)
Background: Aim: The aim of the present study is to assess and compare the efficacy of Macintosh laryngoscope with C-MAC video laryngoscope in attenuating the hemodynamic stress responses to laryngoscopy and endotracheal intubation. Subjects and Methods: A total of 60 patients of ASA grade I or II who were admitted in the hospital for general anaesthesia were included in the study. The total number of patients was randomly divided into two groups containing 30 patients each. In one of the group the endotracheal intubation was performed using the Macintosh laryngoscope while in the other group the endotracheal intubation was performed using the C-MAC video laryngoscope. After successful completion of the intubation process the various hemodynamic parameters were constantly recorded at regular time interval for any sign of hemodynamic response among the patients post intubation. Results: Hemodynamic parameters such as systolic, diastolic and mean arterial pressures and mean heart rate were found to be significantly higher among the Macintosh laryngoscope group in comparison to the C-MAC group. However, no significant difference was observed in the percentage of oxygen saturation among the two groups. The time taken for glottis view and total time taken for intubation was found to be significantly higher among the patients intubated with Macintosh laryngoscope in comparison to C-MAC laryngoscope. The increase in the total time taken for intubation was significantly found to increase the hemodynamic response among the patients signifying the increased risk of hemodynamic complications among patients intubated with Macintosh laryngoscope. Cormack-Lehane grading was found to be higher among the patients intubated with the Macintosh laryngoscope which might have resulted in the increased intubation time among the patients intubated with Macintosh laryngoscope. The percentage of successful intubation at the first attempt was also found to be higher in the C-MAC laryngoscope group in comparison to the Macintosh group.The percentage of glottis opening (POGO) was found to increase significantly with C-MAC video laryngoscope in comparison to the Macintosh laryngoscope. Conclusion: The study concluded that video guided C-MAC laryngoscope was a better alternative to conventional Macintosh laryngoscope with decreased hemodynamic response and increased successful intubation among the patients.